Impact of coronavirus disease on the management of lower urinary tract symptoms and voiding dysfunction. Issue 2 (20th March 2022) - Can, Osman; Otunctemur, Alper
Abstract : Purpose of review: Coronavirus disease (COVID-19) has caused a crisis in the entire healthcare system since its emergence. The urgency and priority of various diseases have impacted the medical and surgical treatment in this period. We aim to review the impact of COVID-19 on lower urinary tract symptoms (LUTS) and management. Recent findings: There may be a relationship between COVID-19 and de novo or increased LUTS. Patients with LUTS should also be evaluated for COVID-19. Management of diseases has varied during the COVID-19 due to the density of the pandemic. Virtual consultations can mitigate patients who are postponed or cancelled, such as patients with LUTS. Patients suffering voiding dysfunction may manage with oral medications such as alpha blocker and 5-alpha reductase inhibitor via telemedicine. Minimally invasive procedures with a low risk of complications and a short hospitalization time should be considered in complicated cases such as the inability to catheterize. Summary: Telemedicine should be implemented on managements of noncomplicated LUTS and voiding dysfunction. Each centre can schedule its LUTS management approach according to the density of pandemic. Virtual consultations need to be developed to compete with face-to-face consultations.